Legal Analysis Of The Cancellation Of Land Ownership Certificates (Shm) Resulting From Redistribution Programs In Cikopomayak And Neglasari, Jasinga District, Bogor Regency - Farid Abdul Mumin; Sri Hartini; Prihatini Purwaningsih (JURNAL MAHASISWA YUSTISI, 2026)
This study examines the legal basis, administrative procedures, and grounds for the cancellation of Land Ownership Certificates (Sertifikat Hak Milik/SHM) originating from an agrarian redistribution program in the villages of Cikopomayak and Neglasari, Jasinga District, Bogor Regency. Using a normative empirical legal method, the research analyzes the conformity of the redistribution process with existing regulations and evaluates the administrative defects that resulted in the revocation of more than 300 certificates. Data were collected through statutory analysis, literature review, and supporting field documentation. The findings demonstrate that the issuance of SHM was inconsistent with Presidential Regulation No. 86 of 2018 and Government Regulation No. 24 of 1997, primarily due to inaccurate subject–object data, invalid nominative lists, and weak field verification. The cancellation executed through Letter No. B/MP.01.02/325-32.01.100/III/2025 was legally valid based on Ministerial Regulation of ATR/BPN No. 9 of 1999 under the doctrine of contrarius actus. The study emphasizes the importance of administrative due diligence in land registration and calls for stronger verification mechanisms to prevent future disputes.